Pengamatan Loyalitas Merek Obat Herbal Berdasarkan Kemasan dan Harga - Rafadi Khan Khayru; RR Nugrahini Susantinah Wisnujati; Didit Darmawan; Fayola Issalillah (Jurnal Simki Economic, 2021)
Standardized herbal medicine is one type of traditional medicine that is made through a manufacturing process and packaged according to consumer behavior in modern times which is full of practical and easy lifestyles. Consumer behavior needs to be observed in the midst of offering a variety of product brands. Competition between brands causes marketers to face the challenge of gaining brand loyalty from customers. The main objective of this study is to investigate the impact of packaging and price on brand loyalty. This quantitative causal study set 65 samples. Data analysis begins with a brief descriptive examination of the composition of the sample followed by validity and reliability tests. To test the predictive relationship, multiple regression analysis was used using SPSS version 26.0 software. From the regression analysis showed a significant positive effect of packaging on brand loyalty. In addition, a significant positive effect is also shown by the price variable on brand loyalty.